Mathematical modelling and analysis of elite athletes` sprint data to study the rate and regulation of ATP during a maximal exercise of short duration - Chuckravanen, D.; Ahlimale, L.; Rajbhandari, S. (PeerJ, 2018)
According to the energy supply/energy depletion model, it is not clear how the depletion of substrates (adenosine triphosphate) affects sprint performance. Therefore, this research was conducted to find out how the human organism regulates the amount and the rate of adenosine triphosphate to observe how these factors affect performance specifically during a maximal exercise of short duration.It was found there was a causal relationship between percentage of PCr and speed which might affect sprint performance.The percentage of chemical energy derived from the anaerobic energy system was found to be 95% for 100-m sprint running. The rate constant for the PCr anaerobic metabolic energy process (0.31s-1) was found to be greater than that of the oxygen-independent glycolysis metabolic process (0.11s-1) and these rate constants affect sprint performance.